Pembuatan sabun cuci piring untuk rumah tanggga - Efi said Ali; Asmara Sari (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2024)
Sei Sikambing C area, Medan Helvetia, Medan, North Sumatra, is where the Al Husna community lives. The group actively participates in various activities to improve the quality of life of its members and maintain their well-being in daily life. Pering laundry soap made from natural ingredients such as clay and whiting is essential for the community's economy. Since soap is used naturally by every household, it costs money. This research method uses the interview method and direct participation in experiments. The research aims to transfer knowledge regarding the manufacture of dish soap